PLCβs are recruited to the plasma membrane in macrophages by both Gβγ and Gα q - Maria E. Falzone; Priyam Banerjee; Roderick MacKinnon (Proceedings of the National Academy of Sciences, 2026)
PLCβ enzymes cleave PIP2 from the plasma membrane, producing IP3 and DAG, which regulate intracellular Ca 2+ levels and protein kinase C activity, respectively. They are regulated by GPCR signaling through the G proteins Gβγ and Gα q and have been shown to function as coincidence detectors for dual stimulation of Gα q - and Gα i -coupled receptors via these G proteins. PLCβs are aqueous-soluble enzymes, but partition onto the membrane surface to access their lipid substrate. We previously demonstrated that membrane recruitment and orientation of the catalytic core on the membrane surface underlie Gβγ-dependent regulation of PLCβ enzymes. Using macrophages as a model system, where PLCβ signaling is essential for responses to infection and tissue injury, we investigated the contribution of Gβγ-dependent regulation and membrane recruitment of PLCβ in the context of endogenous signaling. By measuring Ca 2+ mobilization, we demonstrate that both Gα i - and Gα q -coupled receptors independently stimulate PLCβ activity. Using total internal reflection fluorescence and stimulated emission depletion microscopy, we demonstrate that most of the PLCβ3 in the cell is localized away from the plasma membrane at rest but is rapidly recruited to the plasma membrane upon stimulation by both Gα i - and Gα q -coupled receptors, illustrating that both Gβγ and Gα q recruit PLCβ to the plasma membrane. These results support an updated model for G protein–dependent regulation of PLCβ enzymes, where Gβγ-induced regulation in the absence of Gα q can occur and is apparently dictated by the local concentration of receptor, G proteins, and PLCβ.